Environmental Crisis: A Global Threat of Human Security - Winarno, Budi (Universitas Muhammadiyah Yogyakarta, 2017)
Global warming and climate change are not more than an environmental crisis in the era of neoliberal globalization. This has been a global issue, and in the same time, it has been gradually becoming a global threat of human security. Global awareness among leaders of the countries in the world, and among international communites, are needed to stand together in order to strenghening regional organization and international regime solving this threat of environmental crisis. A global awareness and cooperation among emerging and developed countries are needed to rise their polical will substantially, and most important is to rule out polical economy interest of the developed countries in order to bring about regional organizations and international regime of global environment having more capacity to solve environmental crisis